The Gap : Selected Abstract Art from Belgium - Tuymans, Luc; Ardalan, ziba; De Baere, Bart; D'hooghe, Joris; Drake, Cathryn; Fuenmayor, Jesús; Leitao, Bruno; Loock, Ulrich; Pratt, Ken; Bex, Flor; Mayne, Kate Christina; Parasol unit foundation for contemporary art, London; et al. (London : Parasol unit, 2015)
Alÿs, Francis ; Mees, Guy ; Arocha, Carla ; Schraenen, Stéphane ; Leblanc, Walter ; Robijns, Gert ; De Keyser, Raoul ; Segers, timothy ; Lohaus, Bernd ; Boy & Erik Stappaerts ; Bertrand, Gaston ; Van Snick, Philippe ; Cortier, Amédée ; Vermeersch, Pieter ; Verheyen, Jef
Parasol Unit Foundationan for Contemporary Art, London, 9 September - 6 December 2015 / M HKA, Antwerpen, 19 Februari - 29 Mei 2016
kunstcatalogus
Keywords: België